Application of the European‐modified dental clinical learning environment inventory (DECLEI) in dental schools in Riyadh, Saudi Arabia. (24th June 2016) - Halawany, H. S.; Al‐Jazairy, Y. H.; Al‐Maflehi, N.; Abraham, N. B.; Jacob, V.
Abstract: Aim: The aim of this study was to evaluate undergraduate dental students' self‐perceptions of their clinical dental environment using a valid, concise and more practical version of the Dental Clinical Learning Environment Inventory (DECLEI) questionnaire. Materials and methods: The 24‐item DECLEI was self‐administered to fourth‐ and fifth‐year undergraduate dental students from public and private dental schools in Riyadh, Saudi Arabia, during the 2014—2015 academic year. Factor analysis revealed three underlying factors associated with the clinical learning environment. Independent sample t ‐tests were used to evaluate any associations amongst the items, the factors, the total DECLEI score and other demographic variables. For the scoring system, 6‐point Likert scale responses were scored on a 100% scale ranging from excellent to poor. Results: The mean DECLEI total score was 64.1 (good) of 100. Amongst the factors, the highest mean score, 71.3 (good), was obtained for the patient interactions and professionalism, and the lowest mean score, 50.2 (moderate), was observed for all the negatively worded statements in the DECLEI. The instrument exhibited good discriminant validity as it was able to record significant differences between genders and between public and private institutions in the total DECLEI, the factors and most of the items scored. Conclusions: The new DECLEI scale identified several areas of strength and some aspects that could be improved. Overall, the dental students rated the clinical undergraduate programme as more positive than negative.